(untitled) (Papeles, 2024)
Introduction: This study investigates the potential enhancement of the key competency of cultural awareness and expression in English as a Foreign Language (EFL) by applying an integrated game-based learning (GBL) methodology combined with literature.Methodology: Utilizing a qualitative approach, a didactic sequence was implemented in a 3rd ESO class comprising 30 students. Results and Discussion: The findings indicate that GBL and literature can effectively foster key competencies and foundational EFL skills in an engaging and motivational manner. Despite the limited timeframe, students demonstrated an increased understanding of British culture and the short detective story subgenre while naturally expanding their vocabulary and grammatical skills. Additionally, the heightened motivation observed among students highlights the importance of active learning. Conclusion: The practical implications of this research are inspiring, offering valuable insights for educators and policymakers and motivating further studies in this area.